ACUTE EFFECTS OF GUARANA ON PHYSIOLOGICAL RESPONSES, EXERTION, AND PERFORMANCE: A SYSTEMATIC REVIEW AND META-ANALYSIS - Barbosa, Igor Martins; Weber, Gabriel Rigo; Glanzel, Marcelo Henrique; Mello, Carlos Fernando de (Vivências, 2026)
We aimed to perform a systematic review with meta-analysis of studies that tested the acute effects of guarana supplementation or guarana-added compounds on physiological responses, perceived exertion and exercise performance in healthy adults. This review (CRD42021249569) was performed according to Cochrane recommendations, with searches performed in electronic databases (PubMed, Web of Science, Embase, SportDiscus, and BIREME). Syntheses of data from included studies were performed, and the RoB-2 tool was used to assess the risk of bias. Assessed outcomes were: 1) perceived exertion; 2) exercise performance parameters: peak power (PPO), fatigue, speed, strength, total work and vertical jump height; 3) physiological parameters: heart rate (HR), respiratory exchange ratio (RER), maximal oxygen uptake (VO2max), peak oxygen uptake (VO2peak), glucose and lactate threshold. Available data were pooled through meta-analysis. A significant effect was observed for reduced perceived exertion (SMD: -1.32; 95% CI: -1.85 to -0.79; p < 0.01; I² = 36%), while no effects were detected on heart rate (SMD: -0.18; 95% CI: -0.77 to 0.42; p = 0.56; I² = 0%) following guarana supplementation during exercise. Qualitative analysis indicated that guarana supplementation led to a reduction in fatigue levels (25.30%), an increase in peak power output (PPO) during anaerobic exercise (2.57%), and an increase in total work performed (4%). However, no effects were observed on PPO during aerobic exercise, VO2max, VO2peak, glucose levels, respiratory exchange ratio (RER), lactate threshold, vertical jump performance, or agility tasks.